Partnership dynamics and entry into parenthood: Comparison of Finnish birth cohorts 1969-2000 - Rahnu Leen; Jalovaara Marika (ELSEVIER SCI LTD, 2025)
During the past decade, the stability of close-to-replacement-level fertility ended in all Nordic countries, with its decline to the lowest level in Finland. It is unclear whether and how partnership dynamics have changed, and whether they play a role in fertility developments. We focus on the patterns and associations between the for-mation and stability of co-residential partnerships and first birth among Finnish women and men, and on whether and how these associations have changed across birth cohorts. We utilise total population register data on persons born between 1969 and 2000 in Finland, and adopt the event history method. Our results indicate that half of the women formed their first co-residential partnerships by the age of 22 years. Cohorts born in the early 1990s were the first to delay the formation of non-marital first partnerships. In contrast, first births are increasingly postponed, and the proportion of women and men, who become parents, has declined across recent cohorts. Among men, we observe higher median ages for family formation events and higher likelihoods of not forming a family. As a result of fertility decline and increase in partnership instability, for the first time, the probability of separation is higher than that of first births among partnered women born in the 1990s. Our findings show that at a behavioural level, the once close link between partnership formation and parenthood has progressively eroded across consecutive birth cohorts. Together with the ongoing tendency to delay first births, decreasing partnership stability, and first indications of delaying partnership formation, the potential of wit-nessing a marked increase of fertility levels in the near future is delimited. Our study's results contribute to a better understanding of the demographic mechanisms behind the decline in fertility in Finland, over the recent decade.